Revisiting catalytic performance of supported metal dimers for oxygen reduction reaction via magnetic coupling from first principles - Yu, Linke; Li, Fengyu; Zhao, Jingxiang; Chen, Zhongfang (Advanced Powder Materials, 2022)
In this study, we selected 10 Co-based double-atom catalysts (DACs) catalysts, namely CoMN6-gra(OH) (M ​= ​Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn), and investigated their oxygen reduction reactions (ORR) catalytic performances with/without considering the magnetic coupling by means of density functional theory (DFT) calculations. It was found that CoNiN6-gra(OH), CoCuN6-gra(OH), and CoZnN6-gra(OH) exhibit good catalytic activity of ORR (with low overpotentials of 0.33, 0.34 and 0.23 ​V, respectively) when the magnetic coupling is considered. In particular, magnetic changes in CoMN6-gra(OH) candidates play a vital role in their ORR catalytic activity. Interestingly, the d-band center can be utilized to well rationalize the ORR catalytic activity. This work highlights the importance of considering the magnetic coupling to well predict the activity of ORR catalysts, and discloses that the manipulation of the magnetic coupling between transition metal atoms is an emerging and powerful approach for the development of high-performance electrocatalysts for ORR and other related reactions. [Display omitted]